Azido-galactose outperforms azido-mannose for metabolic labeling and targeting of hepatocellular carcinoma. (1st August 2019) - Wang, Hua; Liu, Yang; Xu, Ming; Cheng, Jianjun
Abstract : Azido-galactose can metabolically label liver cancer cells with azido groups, for subsequent targeted delivery of therapeutics via efficient Click chemistry. Abstract : Metabolic glycoengineering of unnatural monosaccharides provides a facile method to label cancer cells with chemical tags for glycan imaging and cancer targeting. Multiple types of monosaccharides have been utilized for metabolic cell labeling. However, the comparison of different types of monosaccharides in labeling efficiency and selectivity has not been reported. In this study, we compared N -azidoacetylgalactosamine (GalAz) and N -azidoacetylmannosamine (ManAz) for metabolic labeling of HepG2 hepatocellular carcinoma in vitro and in vivo . GalAz showed higher labeling efficiency at low concentrations, and outperformed ManAz in metabolic labeling of HepG2 tumors in vivo . GalAz mediated labeling of HepG2 tumors with azido groups significantly improved the tumor accumulation of dibenzocyclooctyne (DBCO)–Cy5 and DBCO–doxorubicin conjugate via efficient Click chemistry. This study, for the first time, uncovered the distinct labeling efficiency and selectivity of different unnatural monosaccharides in liver cancers.